OPERATORS EXPOSURE TO WHOLE-BODY VIBRATION WHILE PERFORMING FOREST SOIL PREPARATION BY BULLDOZER AND HYDRAULIC EXCAVATORS - dos Santos, Lucas Carvalho; Lopes, Eduardo da Silva; MARTINS, ALYSSON BRAUN; Rodrigues, Carla Krulikowski (Floresta, 2021)
The levels of exposure whole-body vibration (WBV) while performing mechanized soil preparation operations are concerning due to the exposure time of operators at their work stations, adverse terrain topography, and types of wheels on the machines used. Thus, this study aimed to evaluate the exposure to WBV in bulldozers and hydraulic excavators in performing soil preparation for forest plantation in order to identify possible ergonomic problems and propose improvements in working conditions. The study was carried out in Paraná State, Brazil, in a Eucalyptus urophylla × Eucalyptus grandis stand hybrid, being registered with use of a vibration meter and triaxial accelerometer coupled to the seat of the machines, the resulting acceleration to normalized exposure (aren) and the resulting vibration dose (VDVR) for a period of 8 working hours, following the Occupational Hygiene Standard 09. The results showed aren and VDVR values of 1.0 m s-2 and 18.3 m s-1.75 in the bulldozer, while in the hydraulic excavator it was 0.7 m s-2 and 13.5 m s-1.75, respectively, with a statistically significant difference between the machines by the Wilcoxon test for independent samples (α ≤ 0.05). The WBV levels were above the action level and below the exposure limit in both machines, with the bulldozer showing values above the uncertainty level. Therefore, substituting machines specifically designed for soil preparation and improvements in work organization are measures indicated to reduce ergonomic problems.